HAKIKAT MANUSIA DALAM FILSAFAT PENDIDIKAN ISLAM - Sri Nilawati (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
The essence of man in the perspective of Islamic education that man as a creature of God who has a certain uniqueness and certain, talking about the study of philosophy is something very important and fundamental that can determine human life searching for the essence of human nature that can not only be understood in basic thinking, has 2 aspects of physical and spiritual aspects that include: passion, reason, qolbu and ruh. But basically that is from within man is the foundation when we understand human nature by associating that understanding with nature, activity and process of education executed and aims to be able to develop human personality. The ultimate goal of education is personal excellence based on self-realization, namely to realize the potential that already exists within the human being in the form of moral potential, skills and physical development.